Colored high-performance water permeable brick and preparation method thereof

By using metakaolin and magnetic stirring + ultrasonic dispersion technology in permeable bricks, nanocellulose is evenly dispersed, combining high-hardness aggregates and UHPC-based bonding materials, the problems of low strength and poor durability of permeable bricks are solved, and high performance is achieved The preparation of permeable bricks and uniform coloring of the surface layer are suitable for engineering applications.

CN119263748APending Publication Date: 2025-01-07河南省第二建设集团有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411804832.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing permeable bricks have low strength and poor durability, which leads to limited promotion and application in actual projects. The undispersed nanocellulose leads to fiber agglomeration that affects the strength of concrete, making it difficult to promote the carbonization curing method on a large scale.

Method used

Metakaolin is used as the auxiliary gelling material base, and nanocellulose is uniformly dispersed into the cement mortar through magnetic stirring and ultrasonic dispersion technology, and the dye is evenly distributed on the surface layer by collaborative dispersion method, combining high-hardness aggregate and UHPC base Adhesive material to improve the strength and appearance quality of permeable bricks.

Benefits of technology

The high compressive strength and flexural strength of permeable bricks are achieved, the permeability coefficient is significantly improved, the surface layer is uniform and bright, which is convenient for automatic large-scale production, and is suitable for engineering fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263748A_ABST
    Figure CN119263748A_ABST
Patent Text Reader

Abstract

The invention discloses a colored high-performance water permeable brick and a preparation method thereof. Bauxite is adopted as coarse aggregate of the bottom layer material, superfine auxiliary cementing materials metakaolin and silica fume are used in a matched mode, the overall strength of the aggregate binder is guaranteed, in addition, a small amount of nanocellulose is added, and the bonding strength between aggregates is further enhanced. The surface layer material adopts quartz sand as aggregate, the binder raw material adopts white cement, metakaolin and white silica fume, and is matched with a powdery concrete coloring agent, and the coloring agent is added into the surface layer mixed material based on an ultrasonic dispersion technology before the brick body is not formed, so that the surface layer of the water permeable brick is uniformly and stably colored. The water permeable brick subjected to pressure forming and curing has good strength, and the high-strength cement-based binder ensures reliable connection among aggregates; the bauxite is used as a high-strength aggregate, so that the strength of the whole water permeable brick is better improved; and the nano cellulose plays a bridging role, so that the overall toughness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a colored high-performance permeable brick and a preparation method thereof. Background Art

[0002] Permeable bricks are an important part of sponge cities. They can effectively improve the rainwater permeability of urban roads and alleviate waterlogging problems. Permeable bricks are designed with a lower slurry-aggregate mass ratio to achieve a porous molding effect and better permeability. However, due to the low dosage of cement slurry, the bond between aggregates is not tight enough, which in turn affects the performance of permeable bricks. The published permeable bricks have the disadvantages of low strength and poor durability, which seriously restricts their promotion and application in actual projects and is not conducive to the construction of "sponge cities".

[0003] Publication No. CN118271032A discloses a method for preparing high early strength carbon-fixed permeable concrete. The application uses UHPC-based cementitious materials as base binders, bauxite as coarse aggregate, and solid carbonization curing technology to obtain permeable concrete with a compressive strength of 25MPa~30MPa and a permeability coefficient of 0.3~0.4cm / s. However, the flexural strength of the permeable concrete prepared by this method is relatively low, and the direct addition of nanocellulose into the stirring without dispersion treatment will cause fiber agglomeration, which will affect the strength of the concrete and fail to exert its toughening advantage. At the same time, the carbonization curing method cannot be widely promoted in actual production at this stage.

[0004] In view of the above shortcomings, the present invention adopts the synergistic dispersion technology, uses metakaolin as the auxiliary cementitious material base, and uses the linkage of magnetic stirring and ultrasonic dispersion to evenly disperse the nanocellulose into the cement mortar matrix. At the same time, the surface coloring also adopts the synergistic dispersion method to evenly distribute the dye, ensuring that the surface color of the permeable brick is bright and uniform. Summary of the invention

[0005] In view of the shortcomings of the existing technology, this technology specially adopts high-hardness aggregates and UHPC-based bonding materials to optimize and improve the common problems of low strength and poor durability of existing permeable bricks; at the same time, a new dye synergistic dispersion method is used to evenly color the surface layer of the permeable bricks during the preparation process, further improving the visual quality of the permeable bricks.

[0006] The present invention provides a colored high-performance permeable brick, comprising a base material and a surface material, wherein the base material comprises cement, metakaolin, silica fume, bauxite, nanocellulose, water and a water reducing agent; and the surface material comprises cement, metakaolin, silica fume, quartz sand, water, dye and a water reducing agent.

[0007] The present invention uses bauxite coarse aggregate in the bottom layer material. It is composed of corundum and mullite with stable chemical properties. The mechanical properties (strength, hardness, durability, etc.) of bauxite coarse aggregate are significantly better than those of conventional aggregates such as granite and limestone. At the same time, bauxite contains a high content of Al2O3, which supplements the activity of the cementitious material and ensures the bonding between bauxite and the cement mortar matrix; in addition, bauxite contains interconnected pores, which can play a role in aggregate internal curing and further promote hydration reaction.

[0008] In order to improve the toughness of the substrate, the present invention uses nanocellulose in the bottom material, which plays a bridging role in the bonding between the slurry and the aggregate, can effectively inhibit the generation of micro cracks, and make the prepared permeable brick have a flexural strength of up to 9MPa.

[0009] Furthermore, in the bottom layer material, by mass, cement is 190-200 parts, kaolin is 30-50 parts, silica fume is 0-30 parts, bauxite is 1000-1400 parts, nanocellulose is 0-1 part, water reducer is 8-16 parts, and water is 38-54 parts.

[0010] Furthermore, in the surface layer material, by mass, cement is 475-500 parts, metakaolin is 75-100 parts, silica fume is 0-75 parts, quartz sand is 1000-1400 parts, water is 20-40 parts, water is 95-135 parts, and dye is 15-35 parts.

[0011] Furthermore, in the surface layer material, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​silica fume is ≥12 m 2 / g, whiteness ≥90; in the bottom material, the cement is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15m 2 / g, whiteness ≥90.

[0012] Furthermore, the quartz sand particles range from 0.106 to 0.212 mm; the bauxite particles range from 5 to 8 mm; the water reducer is a polycarboxylate water reducer; the nanocellulose has a diameter of 4 to 10 nm and a length of 1 to 3 m.

[0013] Furthermore, when the colored high-performance permeable brick is implemented, the compressive strength reaches 50MPa, the flexural strength reaches 9MPa, and the permeability coefficient is greater than 4mm / s.

[0014] The present invention also provides a method for preparing colored high-performance permeable bricks, wherein the preparation of the bottom layer material comprises the following steps: S1: Take the raw materials for preparing the bottom layer, including cement, metakaolin, silica fume, bauxite, nanocellulose, water and water reducing agent; depending on the size of the prepared component, preliminarily stir 20%-50% by mass of water, 100% by mass of nanocellulose and 100% by mass of water reducing agent to form a mixed liquid for use; S2: Add the mixed cement, metakaolin and silica fume in a concrete mixer and stir. Then add the mixed solution from step S1 and the remaining water and continue stirring for 2-3 minutes until a plastic cement-based slurry is formed; S3: Add bauxite aggregate and stir for 1-2 minutes to make the slurry in step S2 evenly wrap all the aggregates to obtain the bottom slurry.

[0015] Further, the preparation of the surface layer material comprises the following steps: S1: Take the raw materials for preparing the surface slurry, including cement, metakaolin, white silica fume, quartz sand, water and water reducing agent. Depending on the size of the prepared component, put 20% to 50% by mass of metakaolin, the whole mass of dye, 50%-100% by mass of water, and 100% by mass of water reducing agent into a magnetic stirrer and stir for about 10 minutes to form a preliminary stirring to form a mixed liquid; S2: After being stirred by a magnetic stirrer, take out all the mixed liquid, put it into an ultrasonic disperser, and stir it at a power of 800 W for 10-20 minutes; Through magnetic stirring + ultrasonic dispersion, the dye can be evenly dispersed in the kaolin in the system, which is smaller than cement particles, so that the dye is evenly dispersed, durable, non-fading, and non-sticky. Synergistic dispersion further strengthens the performance advantages of kaolin in the system, allowing kaolin to play a bridging role in the concrete system, optimize the particle distribution in cement-based materials, and improve the strength of aggregate bonding paste.

[0016] S3: Add the mixed solution treated in step S2 into a concrete mixer, and add the remaining cement, water, metakaolin, white silica fume and quartz sand into the concrete mixer and stir for 2-3 minutes until a plastic cement-based slurry is formed to obtain a surface layer slurry.

[0017] Furthermore, the method for preparing colored high-performance permeable bricks comprises the following steps: The bottom layer slurry is placed in a mold and initially pressed to obtain the initially pressed bottom material. The surface layer slurry is placed on top of the initially pressed bottom material, subjected to vibration and pressure molding treatment, and then demolded after curing for 24 hours. After demolding, standard curing is continued to be performed to the specified age to obtain the permeable brick.

[0018] Compared with the prior art, the advantages of the present invention are: 1. Through the method of magnetic stirring + ultrasonic dispersion, the dye can be evenly dispersed in the kaolin in the system, which is smaller than cement particles, so that the dye is evenly dispersed, highly durable, does not fade, and does not stick to hands.

[0019] 2. The synergistic dispersion further enhances the performance advantages of kaolin in the system, allowing kaolin to play a bridging role in the concrete system, optimize the particle distribution in cement-based materials, and improve the strength of aggregate bonding paste.

[0020] 3. The bauxite coarse aggregate used is composed of corundum and mullite with stable chemical properties. Its mechanical properties (strength, hardness, durability, etc.) are significantly better than conventional aggregates such as granite and limestone. At the same time, the high content of Al2O3 in bauxite supplements the activity of cementitious materials and ensures the bonding between bauxite and cement mortar matrix. In addition, bauxite contains interconnected pores, which can play a role in aggregate curing and further promote hydration reaction. The compressive strength of permeable bricks prepared with bauxite as coarse aggregate can reach 50MPa.

[0021] 4. The nanocellulose used plays a bridging role in the bonding between the slurry and the aggregate, improves the toughness of the substrate, and can effectively inhibit the generation of microcracks. The flexural strength of the prepared permeable brick can reach 9MPa.

[0022] Beneficial effects of the present invention: The permeable brick of the present invention is a high-performance permeable brick with high compressive strength and flexural strength. When implemented, the compressive strength can reach 50MPa and the flexural strength can reach 9MPa. At the same time, the bauxite aggregate with a reasonable particle size range selected for the bottom layer of the permeable brick can achieve a permeability coefficient of more than 4mm / s. The dyeing agent coordinated dispersion method used in combination makes the surface layer of the permeable brick evenly colored. It is convenient for automatic large-scale production and has a good application prospect in the engineering field. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart for the preparation of colored high-performance permeable bricks. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention discloses a colored high-performance water-permeable brick, which comprises a bottom layer material and a surface layer material. The bottom layer material comprises cement, metakaolin, silica fume, bauxite, nanocellulose, a water reducer and water; the surface layer material comprises cement, metakaolin, silica fume, quartz sand, a water reducer, water and a dye.

[0026] Among the surface materials, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​silica fume is ≥12 m 2 / g, whiteness ≥90; in the bottom material, cement is PO 52.5 cement; metakaolin specific surface area ≥15 m 2 / g, whiteness ≥ 90. The selection of the above materials is obtained by the inventor after creative experiments and labor, and is not easily thought of by those skilled in the art.

[0027] The quartz sand particles used in this embodiment are in the range of 0.106-0.212 mm; the bauxite particles are in the range of 5-8 mm; the water reducer is a polycarboxylic acid water reducer; the diameter of the nanocellulose is 4-10 nm and the length is 1-3 m. The selection of the above materials is obtained by the inventor after creative experiments and labor, and is not easily thought of by those skilled in the art.

[0028] The colored high-performance permeable bricks prepared in this embodiment have a compressive strength of 50MPa, a flexural strength of 9MPa, and a water permeability coefficient of >4mm / s. The selection of the above materials is obtained by the inventor after creative experiments and labor, and is not easily thought of by those skilled in the art.

[0029] The present invention also provides another embodiment, a method for preparing a colored high-performance permeable brick, wherein the preparation of the bottom layer material comprises the following steps: S1: Take the raw materials for preparing the bottom layer, including cement, metakaolin, silica fume, bauxite, nanocellulose, water and water reducing agent; depending on the size of the prepared component, preliminarily stir the water, nanocellulose and water reducing agent in a proportion that meets the mass ratio to form a mixed liquid for use; S2: Add the mixed cement, metakaolin and silica fume in a concrete mixer and stir; then add the mixed solution in step S1 and the remaining water and continue stirring for 2-3 minutes until a plastic cement-based slurry is formed; S3: Add bauxite aggregate and stir for 1-2 minutes to make the slurry in step S2 evenly wrap all the aggregates to obtain the bottom slurry.

[0030] The preparation of the surface material comprises the following steps: S1: Take the raw materials for preparing the surface slurry, including cement, metakaolin, white silica fume, quartz sand, water and water reducing agent. Depending on the size of the prepared component, put the metakaolin, dye, water and water reducing agent in a good mass ratio into a magnetic stirrer and stir for about 10 minutes to form a preliminary stirring to form a mixed liquid; S2: After being stirred by a magnetic stirrer, take out all the mixed liquid, put it into an ultrasonic disperser, and stir it at a power of 800 W for 10-20 minutes; Through magnetic stirring + ultrasonic dispersion, the dye can be evenly dispersed in the kaolin in the system, which is smaller than cement particles, so that the dye is evenly dispersed, durable, non-fading, and non-sticky. Synergistic dispersion further strengthens the performance advantages of kaolin in the system, allowing kaolin to play a bridging role in the concrete system, optimize the particle distribution in cement-based materials, and improve the strength of aggregate bonding paste.

[0031] S3: Add the mixed solution treated in step S2 into a concrete mixer, and add the remaining cement, water, metakaolin, white silica fume and quartz sand into the concrete mixer and stir for 2-3 minutes until a plastic cement-based slurry is formed to obtain a surface layer slurry.

[0032] Molding maintenance: The bottom layer slurry is placed in a mold and initially pressed to obtain the initially pressed bottom material. The surface layer slurry is placed on top of the initially pressed bottom material, subjected to vibration and pressure molding treatment, and then demolded after curing for 24 hours. After demolding, standard curing is continued to be performed to the specified age to obtain the permeable brick. Example 1

[0033] Preparation of colored high-performance permeable bricks: The surface materials include 475 parts of white cement, 100 parts of kaolin, 50 parts of white silica fume, 1200 parts of quartz sand, 20 parts of water reducing agent, 115 parts of water, and 20 parts of dye.

[0034] The base material includes 200 parts of cement, 40 parts of kaolin, 15 parts of silica fume, 1250 parts of bauxite, 0.3 parts of nanocellulose, 8 parts of water reducer and 40 parts of water.

[0035] The cement used for the surface layer is PO 52.5 white cement with a whiteness of ≥85; the cement used for the bottom layer is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the surface layer white silica fume specific surface area ≥12 m 2 / g, whiteness ≥90.

[0036] The quartz sand particles range from 0.106 to 0.212 mm; the bauxite particles range from 5 to 8 mm; the water reducer is a polycarboxylic acid water reducer; the nanocellulose has a diameter of 4 to 10 nm and a length of 1 to 3 m.

[0037] Preparation of bottom material: S1: Take the raw materials for preparing the bottom layer, and depending on the size of the prepared component, preliminarily stir 20%-50% by mass of water, 100% by mass of nanocellulose, and 100% by mass of a water reducer in the ratio to form a mixed liquid for use.

[0038] S2: Add the cement, metakaolin and silica fume in the mix ratio into a concrete mixer and stir. Then add the mixed solution in step S1 and the remaining water and continue stirring for 2-3 minutes until a plastic cement-based slurry is formed.

[0039] S3: Add bauxite aggregate and stir for 1-2 minutes to make the slurry in step S2 evenly wrap all the aggregates to obtain the bottom slurry.

[0040] Preparation of surface materials: S1: Take the raw materials for the preparation of the surface slurry, and depending on the size of the prepared component, put 20% to 50% by mass of kaolin, all the mass of dyes, 50%-100% by mass of water, and 100% by mass of water reducer in the ratio into a magnetic stirrer for about 10 minutes to form a preliminary stirring to form a mixed liquid. The color of the surface layer can be selected according to the needs. The colorant is ferroferric oxide / ferric oxide powder. The recommended mixing ratio is 5%-10% of the cement dosage. The actual coloring effect can be determined by pre-trial mixing.

[0041] S2: After being stirred by a magnetic stirrer, take out all the mixed liquid, put it into an ultrasonic disperser, and stir it at a power of 800 W for 10-20 minutes.

[0042] S3: Add the mixed solution treated in step S2 into a concrete mixer, and add the remaining cement, water, metakaolin, white silica fume and quartz sand into the concrete mixer and stir for 2-3 minutes until a plastic cement-based slurry is formed to obtain a surface layer slurry.

[0043] Molding maintenance: The bottom slurry is placed in a mold, and the mold can be set according to the preset shape of the permeable brick. For example, the shape of the mold can be adjusted according to actual needs.

[0044] Initial pressing is performed to obtain the initial pressed base material, and the surface layer slurry is placed on the top of the initial pressed base material, subjected to vibration and pressure forming treatment, and then demolded after curing for 24 hours. After demolding, standard curing is continued to be performed to the specified age to obtain the permeable brick. Example 2

[0045] Preparation of colored high-performance permeable bricks: The surface materials include 500 parts of white cement, 80 parts of kaolin, 45 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0046] The base material includes 190 parts of cement, 47 parts of kaolin, 18 parts of silica fume, 1200 parts of bauxite, 0.4 parts of nanocellulose, 8 parts of water reducer and 40 parts of water.

[0047] The cement used for the surface layer is PO 52.5 white cement with a whiteness of ≥85; the cement used for the bottom layer is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the surface layer white silica fume specific surface area ≥12 m 2 / g, whiteness ≥90.

[0048] The quartz sand particles range from 0.106 to 0.212 mm; the bauxite particles range from 5 to 8 mm; the water reducer is a polycarboxylic acid water reducer; the nanocellulose has a diameter of 4 to 10 nm and a length of 1 to 3 m.

[0049] The preparation steps are the same as those in Example 1. Example 3

[0050] The surface layer materials include 490 parts of white cement, 90 parts of kaolin, 30 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0051] The base material includes 190 parts of cement, 50 parts of kaolin, 17 parts of silica fume, 1300 parts of bauxite, 0.5 parts of nanocellulose, 8 parts of water reducer and 40 parts of water.

[0052] The cement used for the surface layer is PO 52.5 white cement with a whiteness of ≥85; the cement used for the bottom layer is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the surface layer white silica fume specific surface area ≥12 m 2 / g, whiteness ≥90.

[0053] The quartz sand particles range from 0.106 to 0.212 mm; the bauxite particles range from 5 to 8 mm; the water reducer is a polycarboxylic acid water reducer; the nanocellulose has a diameter of 4 to 10 nm and a length of 1 to 3 m.

[0054] The preparation steps are the same as those in Example 1. Example 4

[0055] The surface layer materials include 485 parts of white cement, 93 parts of kaolin, 32 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0056] The base material includes 200 parts of cement, 50 parts of kaolin, 20 parts of silica fume, 1150 parts of bauxite, 0.4 parts of nanocellulose, 8 parts of water reducer and 40 parts of water.

[0057] The cement used for the surface layer is PO 52.5 white cement with a whiteness of ≥85; the cement used for the bottom layer is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90; the surface layer white silica fume specific surface area ≥12 m 2 / g, whiteness ≥90.

[0058] The preparation steps are the same as those in Example 1. Comparative Example 1

[0059] The surface layer materials include 475 parts of white cement, 100 parts of kaolin, 50 parts of white silica fume, 1200 parts of quartz sand, 20 parts of water reducing agent, 115 parts of water, and 20 parts of dye.

[0060] The base material includes 200 parts of cement, 40 parts of metakaolin, 15 parts of silica fume, bauxite is replaced by limestone and taken to be 1250 parts, 0.3 parts of nanocellulose, 8 parts of water reducer, and 40 parts of water.

[0061] The preparation steps are the same as in Example 1. Comparative Example 2

[0062] The surface layer materials include 500 parts of white cement, 80 parts of kaolin, 45 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0063] The base material includes 190 parts of cement, 47 parts of kaolin, 18 parts of silica fume, 1200 parts of bauxite, 8 parts of water reducer and 40 parts of water.

[0064] The preparation steps are the same as in Example 1. Comparative Example 3

[0065] The surface layer materials include 490 parts of white cement, 90 parts of kaolin, 30 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0066] The base material includes 190 parts of cement, 50 parts of kaolin, 17 parts of silica fume, bauxite is replaced by basalt and takes 1300 parts, nanocellulose is 0.5 parts, water reducer is 8 parts, and water is 40 parts.

[0067] The preparation steps are the same as in Example 1. Comparative Example 4

[0068] The surface layer materials include 485 parts of white cement, 93 parts of kaolin, 32 parts of white silica fume, 1200 parts of quartz sand, 25 parts of water reducing agent, 105 parts of water, and 20 parts of dye.

[0069] The base material includes 200 parts of cement, 50 parts of limestone powder, 20 parts of silica fume, 1150 parts of bauxite, 0.4 parts of nanocellulose, 8 parts of water reducer and 40 parts of water.

[0070] The preparation steps are the same as in Example 1. Test performance

[0071] Performance tests were performed on each embodiment and comparative example, where the compressive strength, flexural strength and water permeability coefficient were after 28 days of standard curing, and the methods were based on "Permeable Pavement Bricks and Permeable Road Panels" (GB / T 25993-2023), "Permeable Concrete" (JC / T 2558-2020), and "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T50081-2019). The test results are shown in Table 1. Table 1

[0072]

[0073] Compared with comparative example 1, Example 1 shows better compressive strength, which is that bauxite is more firmly combined with cement mortar than limestone, and bauxite itself has a higher hardness, which further improves the overall mechanical performance of the permeable brick. By comparing Example 2 with Comparative Example 2, it is found that after adding nanocellulose, Example 2 has better flexural strength and shows better toughness, indicating that nanocellulose plays a better bridging role and inhibits the generation of microcracks when the matrix is ​​tensile. Comparative Example 3, which uses basalt as the bottom coarse aggregate, has lower compressive strength and flexural strength than Example 3, but the crushing index and hardness of basalt itself are closer to bauxite, which may be because bauxite is an active aggregate, and a large amount of Al2O3 inside it participates in the hydration reaction, which enhances the bonding with the matrix and strengthens the interface transition zone of the aggregate-cement mortar matrix. Comparative Example 4 uses limestone powder as a supplementary cementitious material, and its particle size is slightly larger than that of kaolin, which cannot play the effect of optimizing the grading of cementitious materials, indirectly affecting the hydration process, so that the strength of the permeable brick is reduced.

[0074] In summary, the present invention overcomes the shortcomings of low strength, poor durability and poor water permeability of permeable bricks in the prior art. At the same time, the surface coloring in the present invention adopts a collaborative dispersion method to make the dye evenly distributed, ensuring that the color of the surface layer of the permeable brick is bright and uniform, ensuring the visual quality, facilitating automatic large-scale production, and having good application prospects in the engineering field.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A colored high-performance permeable brick, comprising a bottom layer material and a surface layer material, characterized in that: The bottom layer materials include cement, metakaolin, silica fume, bauxite, nano cellulose, water and a water reducing agent; the surface layer materials include cement, metakaolin, silica fume, quartz sand, water, dye and a water reducing agent.

2. A colored high-performance permeable brick as claimed in claim 1, characterized in that: In the bottom layer material, by weight, cement is 190-200 parts, kaolin is 30-40 parts, silica fume is 0-30 parts, bauxite is 1000-1400 parts, nanocellulose is 0-1 parts, water reducer is 8-16 parts, and water is 38-54 parts.

3. A colored high-performance permeable brick as claimed in claim 2, characterized in that: In the surface layer material, by weight, cement is 475-500 parts, kaolin is 75-100 parts, silica fume is 0-75 parts, quartz sand is 1000-1400 parts, water is 20-40 parts, water is 95-135 parts, and dye is 15-35 parts.

4. A colored high-performance permeable brick as claimed in claim 3, characterized in that: In the surface layer material, the cement is PO 52.5 white cement with a whiteness of ≥85; the specific surface area of ​​silica fume is ≥12 m 2 / g, whiteness ≥90.

5. A colored high-performance permeable brick as claimed in claim 4, characterized in that: In the bottom material, the cement is PO 52.5 cement; the specific surface area of ​​the metakaolin is ≥15 m 2 / g, whiteness ≥90.

6. A colored high-performance permeable brick as claimed in claim 5, characterized in that: The quartz sand particles range from 0.106 to 0.212 mm; the bauxite particles range from 5 to 8 mm; the water reducer is a polycarboxylate water reducer; the nanocellulose has a diameter of 4 to 10 nm and a length of 1 to 3 m.

7. A colored high-performance permeable brick as claimed in claim 6, characterized in that: When the colored high-performance permeable brick is implemented, the compressive strength reaches 50MPa, the flexural strength reaches 9MPa, and the permeability coefficient is greater than 4mm / s.

8. A method for preparing a colored high-performance permeable brick according to any one of claims 1 to 7, characterized in that: The preparation of the bottom layer material comprises the following steps: S1: Take the raw materials for preparing the bottom layer, including cement, metakaolin, silica fume, bauxite, nanocellulose, water and water reducing agent; depending on the size of the prepared component, preliminarily stir 20%-50% by mass of water, 100% by mass of nanocellulose and 100% by mass of water reducing agent to form a mixed liquid for use; S2: Add the prepared cement, metakaolin and silica fume to a concrete mixer and stir; then add the mixed solution from step S1 and the remaining water and continue stirring for 2-3 minutes until a plastic cement-based slurry is formed; S3: Add bauxite aggregate and stir for 1-2 minutes to make the slurry in step S2 evenly wrap all the aggregates to obtain the bottom slurry.

9. The method for preparing a colored high-performance permeable brick according to claim 8, characterized in that: The preparation of the surface layer material comprises the following steps: S1: Take the raw materials for preparing the surface slurry, including cement, metakaolin, white silica fume, quartz sand, water and water reducing agent; depending on the size of the prepared component, put 20% to 50% by weight of metakaolin, the whole weight of dye, 50%-100% by weight of water, and 100% by weight of water reducing agent into a magnetic stirrer for 10 minutes to form a preliminary stirring to form a mixed liquid; S2: After being stirred by a magnetic stirrer, take out all the mixed liquid, put it into an ultrasonic disperser, and stir it at a power of 800 W for 10-20 minutes; S3: Add the mixed solution treated in step S2 into a concrete mixer, and add the remaining cement, water, metakaolin, white silica fume and quartz sand into the concrete mixer and stir for 2-3 minutes until a plastic cement-based slurry is formed to obtain a surface layer slurry.

10. The method for preparing a colored high-performance permeable brick according to claim 9, characterized in that: The following steps are also included: The bottom layer slurry is placed in a mold and initially pressed to obtain the initially pressed bottom material. The surface layer slurry is placed on top of the initially pressed bottom material, subjected to vibration and pressure molding treatment, and then demolded after curing for 24 hours. After demolding, standard curing is continued to be performed to the specified age to obtain the permeable brick.

Citation Information

Patent Citations

  • High-performance NCF fiber cement-based composite material and preparation method thereof

    CN116177962A

  • Ultra-high performance concrete containing nano-crystalline cellulose fibers and preparation method of ultra-high performance concrete

    CN117003522A

  • Low-shrinkage high-cohesiveness repair concrete as well as preparation method and application thereof

    CN118206333A

  • Pervious concrete with high early strength and high carbon sequestration content and preparation method of pervious concrete

    CN118271032A

  • methode for manufacturing of precast color concrete pier

    KR1020100072633A